Estudio de factibilidad para la producción y pasteurización de leche bovina en la provincia de Zamora Chinchipe - Freire Mora, Eduardo Daniel (2014)
The industrialization of the dairy in Ecuador and especially in the province of Zamora has less economic potential. Since this creates a new source of income for its practitioners, framed in a culture of quality products at reasonable costs. In the province of Zamora Chinchipe there is little industrial development due to the state and financial institutions have not taken the initiative to fund different projects or provide existing businesses low-interest loans so they can get low-cost products which allows them to be more competitive locally, nationally. Milk production of cows in the area has its principal market in the city of Loja to the company Ecolac collection made in cycles of two to three times a week, causing much of the production is not consumed in the province, absence of a plant of industrialization of the product in the area, creating waste handling and lack of cold chains. As the consumption of milk of poor quality and standard. The productive capacity as MAGAP and UTPL through studies, and with reference Ecolac, performs stockpile two to three days a week with an average of 2700 liters to 6000 liters per trip. And COMPROLACSA company with an average of 1500 to 2500 liters twice a week for collection. Given this last COMPROLACSA is in the process of liquidation of capital assets and closing operational function results in a bigger market for this product industrializing. Also include the excess production not purchased by these companies are sold in informal outlets of different populations or sub derivatives thereof, same q do not have any guarantee of health or industrialization process after the health of the consumer. Most of the population of the province of Zamora as a study of market Fernando Vazquez on "Project feasibility for the implementation of a dairy 6 producer Canton Yantzaza" consume milk dispensing informal, since it comes from vendors of door to door, in plastic containers without prior refrigeration or cold chain for marketing. The processed milk is sold in the province comes Tetra pack, which by its high cost in many cases becomes inaccessible for end users. Although beneficial for traders for the duration thereof and not requiring a cold chain. Given the above circumstances, it is essential to conduct a feasibility study for implementing a pasteurizing dairy company, which has all the guarantees of safety to improve product quality expended in the area. Finally, in terms of profitability although one of the first ideals of the company is to provide quality products based on the highest standards of hygiene and presentation, will also be taken into account to have a profitable business from accounting analysis , Financial and Administrative decision making - Managerial that encourage business development and profitable development. It should be noted that so far there is no formal analysis regarding the cost of owning or starting a business of industrialization of dairy proDucts, for the purpose of serving the Zamora people, with products of higher quality and hygiene standards. Thus, after performing "FEASIBILITY STUDY FOR THE PRODUCTION OF MILK AND BOVINE PASTEURIZATION IN THE PROVINCE OF ZAMORA CHINCHIPE" is evidenced in the need to implement the pasteurizer of milk for the province of Zamora. And they conclude by presenting viable strategies to implement this business.